Analysis of the Conjugate Heat Transfer in a Multi-Layer Wall including an Air Layer - M., Armando Gallegos; C., Christian Violante; B., José A. Balderas; H., Víctor H. Rangel; F., José M. Belman (IntechOpen, 2011)
None